Polar Cryoconite Associated Microbiota Is Dominated by Hemispheric Specialist Genera - Millar, Jasmin L.; Bagshaw, Elizabeth A.; Edwards, Arwyn; Poniecka, Ewa A.; Jungblut, Anne D. (Frontiers in Microbiology, 2021)
Cryoconite holes, supraglacial depressions containing water and microbe-mineral aggregates, are known to be hotspots of microbial diversity on glacial surfaces. Cryoconite holes form in a variety of locations and conditions, which impacts both their structure and the community that inhabits them. Using high-throughput 16S and 18S rRNA gene sequencing, we have investigated the communities of a wide range of cryoconite holes from 15 locations across the Arctic and Antarctic. 25 prokaryotic and nine eukaryotic first-rank phyla were observed in total. The various biotic niches (grazer, predator, photoautotroph, chemotroph), are filled in every location. Significantly, there is a clear divide between the bacterial and microalgal communities of the Arctic and that of the Antarctic. We were able to determine the groups contributing to this difference and the family and genus level. Both polar regions contain a “core group” of bacteria that are present in the majority of cryoconite holes and each contribute >1% of total ASV abundance. Whilst both groups contain Nostoc and Scytonema, the remaining members are specific to the core group of each polar region. Additionally the microalgal communities of Arctic cryoconite holes are dominated by Chlamydomonas whereas the Antarctic cryoconite holes are dominated by Chlorococcales. Therefore cryoconite holes may be a global feature of glacier landscapes, but they are inhabited by regionally distinct microbial communities. Our results are consistent with the notion that cryoconite microbiomes are adapted to differing conditions within the cryosphere.